Associated factors for pulmonary tuberculosis in Coahuila for 2021-2022 period - León-Camacho, A.E.; Cepeda-Nieto, A.C.; Salinas-Aguirre, J.E. (Revista de Ciencias Médicas Torreón, 2025)
The present study focused on analyzing the factors associated with the prevalence of pulmonary tuberculosis in Coahuila during the years 2021 and 2022, by reviewing data on the tuberculosis program platform of the Ministry of Health of the National Epidemiological Surveillance System (SINAVE). 8990 records were analyzed, and 572 cases of pulmonary tuberculosis were confirmed. A significantly higher prevalence was observed in the male population compared to the female. The distribution of confirmed cases was more prominent in adults (27-59 years), followed by older adults (60+ years). Additionally, several risk factors associated with pulmonary tuberculosis were identified. Uncontrolled diabetes stood out as a significant factor, increasing the risk of developing the disease by more than seven times. Malnutrition was also associated with a significantly higher risk, with an increase of approximately thirteen times. Immunosuppression and previous history of tuberculosis were also risk factors, increasing the risk by around five and eight times, respectively. The study revealed an inverse association between the presence of HIV and the risk of tuberculosis, indicating that the presence of HIV could have a protective effect against tuberculosis in the studied population.
Keywords: tuberculosis; uncontrolled diabetes; malnutrition; malnutrition HIV-tuberculosis association